2008
DOI: 10.1016/j.janxdis.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The child behavior checklist broad-band scales predict subsequent psychopathology: A 5-year follow-up

Abstract: The convergence of these results with previous findings based on structured diagnostic interviews suggests that the CBCL broad-band scales can inexpensively and efficiently help identify children at high risk for future psychopathology within a population of children already at risk by virtue of parental psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 32 publications
3
61
0
Order By: Relevance
“…Family aggregate studies indicate that children of anxious parents have an elevated rate of anxiety disorders (Beidel & Turner, 1997;Biederman et al, 1996;Merikangas et al, 1998;Petty et al, 2008;Turner, Beidel, & Costello, 1987) and parents of children with anxiety disorders experience higher rates of anxiety disorders (Last, Hersen, Kazdin, Francis, & Grubb, 1987;Last, Hersen, Kazdin, Orvashel, & Perrin, 1991). A recent modelling study investigating risk factors for childhood anxiety found that anxious rearing significantly predicted symptoms of anxiety disorders at 1 year follow-up and trait anxiety of both parents at 1 year follow-up made independent contributions to child anxiety symptoms at 2-year follow-up (Muris et al, 2011).…”
Section: Parental Psychopathologymentioning
confidence: 99%
“…Family aggregate studies indicate that children of anxious parents have an elevated rate of anxiety disorders (Beidel & Turner, 1997;Biederman et al, 1996;Merikangas et al, 1998;Petty et al, 2008;Turner, Beidel, & Costello, 1987) and parents of children with anxiety disorders experience higher rates of anxiety disorders (Last, Hersen, Kazdin, Francis, & Grubb, 1987;Last, Hersen, Kazdin, Orvashel, & Perrin, 1991). A recent modelling study investigating risk factors for childhood anxiety found that anxious rearing significantly predicted symptoms of anxiety disorders at 1 year follow-up and trait anxiety of both parents at 1 year follow-up made independent contributions to child anxiety symptoms at 2-year follow-up (Muris et al, 2011).…”
Section: Parental Psychopathologymentioning
confidence: 99%
“…There is also a possibility that the association between psychopathology and tobacco smoking may change as the proportion of smokers in the population declines. With less than 20% of the Australian population now smokers [15,16] it may be that the remaining tobacco smokers are more likely to have symptoms of psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, whether the mediational pathway stands in the development of behavioral problems warrants further investigation. When investigating the relationships among personality, stress, and behavioral problems, the influences of depression should be taken into account since depressive disorders or symptoms were found to highly comorbid with other emotional/behavioral problems [8]. In addition, research has indicated that the occurrence of depression might increase the risks of recurrence of depression through enhancing the vulnerability of individuals' personality toward depression, which is known as the scar hypothesis [9].…”
Section: Participantsmentioning
confidence: 99%